Experimentação no ensino de química: uma proposta para o ensino de espectrofotometria de emissão molecular - Lemos, Marcio Peroni [UNIFESP] (2020)
In this research we built a low cost fluorimeter estimated at 80 reais compared to the equipment available on the market with an estimated cost of over 180 thousand reais. This had a simple circuit, based on the detection of light, in the phenomenon of molecular emission spectrometry. After verifying the viability of the low-cost equipment by carrying out tests with it, we proposed an experimental protocol that uses an experiment carried out to determine the quinine content in tonic water. This protocol, with a duration of 4 hours / class, being a prerequisite for participation in a theoretical class (lasting 4 hours / class), was used for the teaching of 21 students of the Science course - degree, from the Federal University of São Paulo. Data collection was also carried out in order to validate this protocol, and pre-and post-test questionnaires, participant observation and an exercise applied at the end of the process were used for data collection. The collected data were classified and organized in a table, for later analysis. The results of the data collection point to an improvement in the students' level of knowledge on the topic. This leads us to conclude that experimentation can be a good alternative and that the built protocol was valid for teaching molecular emission spectrometry. In addition, it was noted that experimentation helped to improve students' practical skills, such as the manipulation and use of glassware, as well as the feasibility of building equipment from studied concepts and phenomena.